(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
Random copolymerizations of L-Lactide with ?-Caprolactone by ring opening polymerization reactions were carried out. A number of copolymers were formed and observed that any composition of copolymer can be formed by changing the feed ratio of the respective monomers. The effect of temperature and time in copolymerization reaction were studied. For their characterization, NMR, IR, DSC and GPC were measured. The stereo-effect of the lactic acid based biodegradable polymers and copolymers for improve thermo-mechanical properties were studied. The obtained copolymers also show stereo-effect like homopolymer. The biodegradability of obtained polymers, copolymers and stereocomplex were studied in three different biodegradation methods; e.g., Enzymatic method, Composting method and Activated Sludge treatment method; and compared to each other. DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11453 Bangladesh J. Sci. Ind. Res. 47(2), 203-210, 2012